2007
DOI: 10.1038/sj.pcan.4500984
|View full text |Cite
|
Sign up to set email alerts
|

Neutral endopeptidase inhibits prostate cancer tumorigenesis by reducing FGF-2-mediated angiogenesis

Abstract: Neutral endopeptidase (NEP) is a cell surface peptidase that catalytically inactivates a variety of physiologically active peptides including basic fibroblast growth factor (FGF-2). We investigated the effect of using lentivirus to overexpress NEP in NEP-deficient DU145 prostate cancer cells. Third-generation lentiviral vectors encoding wild-type NEP (L-NEP), catalytically inactive mutant NEP (L-NEPmu), and green fluorescent protein (L-GFP) were stably introduced into DU145 cells. FGF-2 levels in cell culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…A recent study found that down‐regulation of TGF‐β2 stabilizes endothelial tube formation (DiMaio et al 2014). The up‐regulated MME encodes the membrane metalloendopeptidase/CD10, which inhibits angiogenesis by degrading several angiogenic factors (Kajiyama et al 2005; Horiguchi et al 2008). Expression of some members of the VEGF pathway were down‐regulated.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that down‐regulation of TGF‐β2 stabilizes endothelial tube formation (DiMaio et al 2014). The up‐regulated MME encodes the membrane metalloendopeptidase/CD10, which inhibits angiogenesis by degrading several angiogenic factors (Kajiyama et al 2005; Horiguchi et al 2008). Expression of some members of the VEGF pathway were down‐regulated.…”
Section: Resultsmentioning
confidence: 99%
“…It catalyzes the degradation of various neuropeptides implicated in migration, proliferation and contraction, including atrial naturetic peptide (ANP), enkephalins, substance P, bradykinin, endothelin-1 and angiotensin II 1 . Among growth factors, fibroblast growth factor (FGF) is cleaved by NEP but PDGF and transforming growth factor (TGFβ) are not 3 . In addition to its peptidase activity basic amino acid residues in the tail of NEP contribute to protein–protein interactions resulting in modulation of signaling factors in prostate cancer cell lines 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, NEP has been reported to inhibit angiogenesis in prostate cancer. 46 Further studies are needed to determine whether NEP activity toward other substrates regulates epithelial breast cancer cells or the surrounding tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%